2022
DOI: 10.1088/1361-6463/ac57de
|View full text |Cite
|
Sign up to set email alerts
|

Particle trapping, size-filtering, and focusing in the nonthermal plasma synthesis of sub-10 nanometer particles

Abstract: Low-pressure nonthermal flowing plasmas are widely used for the gas-phase synthesis of nanoparticles and quantum dots of materials that are difficult or impractical to synthesize using other techniques. To date, the impact of temporary electrostatic particle trapping in these plasmas has not been recognized, a process that may be leveraged to control particle properties. Here, we present experimental and computational evidence that, during their growth in the plasma, sub-10 nanometer silicon particles become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…While the gas residence time can be easily determined, estimation of the particle trapping time requires intricate experimental methods capable of detecting individual particles in the reactor. Interestingly, recent Monte Carlo simulations of particle trapping for sub-10 nm NPs have shown that even though considering particle trapping in the reactor results in the synthesis of particles with larger sizes than the no trapping assumption, the average NP size is still linearly dependent on the gas residence time . In Figure b, we experimentally validate this result by controlling the NP diameter in the plasma reactor via adjustment of the gas residence time.…”
Section: Plasma Synthesis Of Size-controlled Crystalline Silicon Nano...supporting
confidence: 57%
See 1 more Smart Citation
“…While the gas residence time can be easily determined, estimation of the particle trapping time requires intricate experimental methods capable of detecting individual particles in the reactor. Interestingly, recent Monte Carlo simulations of particle trapping for sub-10 nm NPs have shown that even though considering particle trapping in the reactor results in the synthesis of particles with larger sizes than the no trapping assumption, the average NP size is still linearly dependent on the gas residence time . In Figure b, we experimentally validate this result by controlling the NP diameter in the plasma reactor via adjustment of the gas residence time.…”
Section: Plasma Synthesis Of Size-controlled Crystalline Silicon Nano...supporting
confidence: 57%
“…Interestingly, recent Monte Carlo simulations of particle trapping for sub-10 nm NPs have shown that even though considering particle trapping in the reactor results in the synthesis of particles with larger sizes than the no trapping assumption, the average NP size is still linearly dependent on the gas residence time. 64 In Figure 2b, we experimentally validate this result by controlling the NP diameter in the plasma reactor via adjustment of the gas residence time. Furthermore, we show the linear relation to gas residence time holds even for particle sizes over 10× the prior studies by Monte Carlo.…”
Section: Crystalline Silicon Nanoparticlesmentioning
confidence: 58%
“…When the flow velocity was increased from 1.5 to 7 m/s, the mean particle diameter decreased from 15.6 to 5.8 nm. This trend is consistent with other reports on plasma synthesis of nanocrystals in similar reactors. High-resolution TEM imaging revealed clear lattice fringes extending to the edges of the particles, indicating particles are single crystals. X-ray diffraction patterns (Figure c) of as-deposited Cr 2 O 3 nanocrystals can be readily indexed to phase-pure α-Cr 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Pure silane and argon enter through the top of the reactor with typical flow rates of 0.2 and 7.5 standard cubic centimeters per minute (sccm), respectively, leading to a gas residence time in the plasma zone of about 2 s. However, because of the electrostatic trapping of particles upstream of the ring electrode that was observed in ref the actual particle residence time in the reactor is expected to be longer. The electrostatic trapping requires that particles grow to a minimum threshold size before being removed from the trap by the gas flow, which causes a size filtering of the particles, leading to a narrow size distribution . The plasma is excited by applying a nominal radiofrequency (RF) power of 200 W at 13.56 MHz to a ring electrode placed 6.5 cm upstream of the lower flange, which serves as the ground electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The electrostatic trapping requires that particles grow to a minimum threshold size before being removed from the trap by the gas flow, which causes a size filtering of the particles, leading to a narrow size distribution. 83 The plasma is excited by applying a nominal radiofrequency (RF) power of 200 W at 13.56 MHz to a ring electrode placed 6.5 cm upstream of the lower flange, which serves as the ground electrode. Nanocrystals are extracted by the gas flow through a 12 × 0.064 mm slit-shaped orifice and injected into the deposition chamber.…”
Section: ■ Methodsmentioning
confidence: 99%